Educational environment of supplementary schools as a factor of formation of older preschooler`s creative-oriented personality - Oleksandr Semenov (Vasyl Stefanyk Precarpathian National University, 2017)
In article the author examines the role of the educational environment in forminga creatively directed personality of the child of the senior preschool age. It was found thateducational environment of out-of-school educational institution has a multicomponentstructure, which consists of interrelated components: creative, gaming, developmental,affective and emotional. Stated that the educational environment of out-of-school educationalinstitutionplays in society especially significant features that give us reason to consider it asan important factor in the formation of the creatively directed personality of the 5th year child.Prospects for further scientific researches are determined in studying the psychological andeducational of creative potential characteristics of personality of the pedagogue in out-ofschooleducational institution. Key words: educational environment of out-of-school educational institutions, thecreatively directed personality of the senior preschooler, components of the educationalenvironment, functions of the educational environment.